2019
DOI: 10.1111/mec.15294
|View full text |Cite
|
Sign up to set email alerts
|

Geographical and temporal variation of multiple paternity in invasive mosquitofish (Gambusia holbrooki, Gambusia affinis)

Abstract: Multiple paternity (MP) increases offspring's genetic variability, which could be linked to invasive species' evolvability in novel distribution ranges. Shifts in MP can be adaptive, with greater MP in harsher/colder environments or towards the end of the reproductive season, but climate could also affect MP indirectly via its effect on reproductive life histories. We tested these hypotheses by genotyping N = 2,903 offspring from N = 306 broods of two closely related livebearing fishes, Gambusia holbrooki and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 92 publications
(154 reference statements)
2
11
1
Order By: Relevance
“…In small and genetically depauperated populations, genetic compensation mechanisms may contribute to increase N b and N e via an increment in the average breeding success of individuals (Beebee 2009;Sánchez-Montes et al 2017), and this in turn may be related with higher polygamy rates (Byrne & Roberts 2012;Gao et al 2019). In our study population, we observed high polygamy rates in both males and females, according to inferred pedigrees.…”
Section: ; Beebeesupporting
confidence: 56%
See 2 more Smart Citations
“…In small and genetically depauperated populations, genetic compensation mechanisms may contribute to increase N b and N e via an increment in the average breeding success of individuals (Beebee 2009;Sánchez-Montes et al 2017), and this in turn may be related with higher polygamy rates (Byrne & Roberts 2012;Gao et al 2019). In our study population, we observed high polygamy rates in both males and females, according to inferred pedigrees.…”
Section: ; Beebeesupporting
confidence: 56%
“…2017), and this in turn may be related with higher polygamy rates (Byrne & Roberts 2012; Gao et al . 2019). In our study population, we observed high polygamy rates in both males and females, according to inferred pedigrees.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To minimize the potentially confounding effect of local conditions on multiple paternity, we randomly sampled 31 pregnant females from 8 different locations to characterize multiple paternity in P. gillii across its South-Western range in Costa Rica. Moreover, many studies on multiple paternity in species with large broods have analyzed only a fraction, or a set number of embryos, per brood (Travis et al, 1990;Greene and Brown, 1991;Girndt et al, 2012 but see Gao et al, 2019), potentially underestimating the absolute number of sires that may have contributed to the broods. To avoid this, we genotyped and analyzed all embryos (N = 1346) to quantify multiple paternity in our 31 P. gillii females.…”
Section: Multiple Paternitymentioning
confidence: 99%
“…Most earlier multiple paternity studies have focused on species with small broods, such as Poecilia reticulata (Kelly et al, 1999;Hain and Neff, 2007;Neff et al, 2008), Heterandria formosa, (Kelly et al, 1999;Soucy and Travis, 2003), Xiphophorus multilineatus (Luo et al, 2005), X. nigrensis (Smith, 2014), and X. birchmanni (Paczolt et al, 2015). Only a few earlier studies focus on species with large broods, i.e., Poecilia latipinna and Gambusia affinis, but most of these only analyze a small part of the actual brood (Travis et al, 1990;Greene and Brown, 1991;Girndt et al, 2012), except for a study by Gao et al (2019) that studied multiple paternity in whole broods of Gambusia affinis and G. holbrooki. Therefore, little is currently known about how the large variation in brood size affects multiple paternity, the number of sires per brood and male reproductive skew within species.…”
Section: Introductionmentioning
confidence: 99%